2020
DOI: 10.1002/jbm.b.34592
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilver composite pNIPAm microgels for the development of antimicrobial platelet‐like particles

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Previous studies have shown that, when incorporated into in vivo wounds, PLPs incorporate with native fibrin forming at wound sites [33]. In a separate set of studies investigating nanosilver composite PLPs in an infected wound model, we did not observe particles in histological sections 9 days post-injury [50], indicating that PLPs are cleared when applied topically; however, detailed studies into the eventual clearance mechanism of PLPs in this application have not yet been performed.…”
Section: Clot Density and Fibroblast Migration Are Enhanced In The Presence Of Plps Within A Platelet-rich Environmentmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous studies have shown that, when incorporated into in vivo wounds, PLPs incorporate with native fibrin forming at wound sites [33]. In a separate set of studies investigating nanosilver composite PLPs in an infected wound model, we did not observe particles in histological sections 9 days post-injury [50], indicating that PLPs are cleared when applied topically; however, detailed studies into the eventual clearance mechanism of PLPs in this application have not yet been performed.…”
Section: Clot Density and Fibroblast Migration Are Enhanced In The Presence Of Plps Within A Platelet-rich Environmentmentioning
confidence: 57%
“…It is also possible that the effect of adding PLPs under this condition are less pronounced than in the hemophilialike condition due to the vastly greater force exerted by native platelets within a clot matrix relative to those exerted by PLPs [33,46]. Nonetheless, in our previous studies investigating the role of PLPs on wound healing outcomes in vivo in a rodent full thickness dermal, we observed significant enhancement when PLPs were applied to the wound, even though this was a healthy model [33,50] with functional platelets, which is likely due to the early influence that PLPs have on network. In these experiments, we found PLPs did not significantly increase clot density in the presence of platelets under normal, healthy conditions; this is likely due to the fact that native platelets act on a faster time scale than PLPs do within fibrin networks [33,46].…”
Section: Clot Density and Fibroblast Migration Are Enhanced In The Presence Of Plps Within A Platelet-rich Environmentmentioning
confidence: 81%
“…Total blood loss quantification over the course of the 10 min injury showed significantly lower total blood loss for animals that received treatment with 15 mg kg −1 FAMCYs (0.0078 ± 0.003 gram blood/gram animal) compared to saline treated animals (0.016 ± 0.004 gram blood/gram animal, p ‐value = 0.0193) (Figure 7). Furthermore, evaluation of total blood loss in animals receiving 15 mg kg −1 FAMCY treatment versus previously published data in total blood loss in animals receiving treatment with previous iterations of platelet‐mimetic particles that utilize either an antibody‐based [ 29 ] or sdFv‐based [ 25 ] targeting motif indicates that FAMCY formulations reduce overall blood loss similarly (≈50%–60% reduction relative to saline controls) to these previous formulations. Minimal differences in total blood loss were seen when comparing saline treatment to bare ULC microgel (0.012 ± 0.004 gram blood/gram animal, p ‐value = 0.7195) and control peptide FAMCYs (0.013 ± 0.002 gram blood/gram animal, p ‐value = 0.8178).…”
Section: Resultsmentioning
confidence: 90%
“…Chee et al incorporated AgNPs within ultra-soft PNIPAm-based platelet-like microgels to mitigate bacterial growth during clot retraction, achieving a wound cloture rate compared to native PLPs and inhibiting microbial proliferation. [6] Uhlig et al incorporated carboxylated PS nanobeads within PNIPAm microgels coated onto glass coverslips and observed enhanced cell adhesion as the carboxylic acid moieties increased the hydrophilicity of the surface. [49] Microgels may also be used to mediate the formation of nanoparticle patterns onto surfaces.…”
Section: Nanoparticle Additionmentioning
confidence: 99%
“…The past two decades have witnessed a rapid increase in the use of hydrogel microparticles (henceforth, "microgels") as surface coatings for advancing filtration, [1][2][3][4] wound dressing, [5][6][7][8] sensing, [9][10][11][12][13] antifouling, [14][15][16] sequestration of chemicals, [17] and controlled delivery applications. [18][19][20][21] The versatility of microgelbased coatings stems from the physicochemical and morphological properties of both microgels and surfaces, the deposition methods, and post-deposition treatments.…”
Section: Introductionmentioning
confidence: 99%